Design and Development of an IoT-Based Household Electrical Energy Monitoring Application for Energy Efficiency - Luluk Suhartini; Fadila Fadila (Journal of Electrical Engineering and Computer (JEECOM), 2026)
Electricity consumption in households is often not properly controlled, which can lead to energy waste and higher electricity bills. Therefore, a system is needed to monitor household electricity usage in real time and provide users with clear information to help them take energy-saving actions. This study designs and develops an Internet of Things (IoT)-based household electricity monitoring application using a PZEM-004T sensor connected to a NodeMCU ESP8266 microcontroller. The measured data, including voltage, current, power, and energy consumption, are transmitted wirelessly to a server and displayed on a custom web-based dashboard without relying on third-party IoT platforms. The application features real-time monitoring and historical consumption records, enabling users to track energy usage trends. Test results show that the system can measure and display data accurately with an average transmission delay of 1–2 seconds, and it helps identify energy-intensive household appliances. Thus, this application can be an effective solution to improve energy efficiency in households.